UPAYA PENGUATAN BRAND TRUST LIPSTIK WARDAH DI PLATFORM TIKTOK LIVE PADA GENERASI Z - Agista Nurul Defani; Diana Aqmala; Ariati Anomsari; Awanis Linati Haziroh (LPPM STIE Muhammadiah Bandung, 2026)
The purpose of this study is to analyze the influence of Customer Experience, Live Streaming, and Influencer Credibility on Brand Trust of Generation Z Wardah lipstick users through TikTok Live. This study uses a quantitative method, with data obtained from 170 Generation Z respondents in Semarang who have watched and interacted directly with the Wardah brand through TikTok live. Data analysis uses the PLS-SEM technique processed using SmartPLS 4 software. The results show that the three independent variables, namely Customer Experience, Live Streaming, and Influencer Credibility, have a positive and significant effect on Brand Trust. This shows that a pleasant Customer Experience, authentic and interactive interactions through live broadcasts, and the credibility of influencers who have similar expertise and values ​​to the audience, can increase consumer trust in the Wardah brand.